What's left of Marxism historiography and the possibilities of thinking with Marxian themes and concepts - What is left of Marxism? Historiography and the possibilities of thinking with Marxian themes and concepts; Zachariah, Benjamin 1972-; Raphael, Lutz 1955-; Bernet, Brigitta 1973- (Politics of historical thinking, 2020)
This series seeks to focus on the politics inherent in historical thinking, professional and non-professional, promoted by states, political organisations, 'nationalities' or interest groups, and to explore the links between political (re-)education, historiography and mobilisation or identity formation.